Post operatory analgesia in caesarean surgery. - Bárbara Lucía Cabezas Poblet; Guyen Cuellar Chang; Rolando T. Espín González; María Antonia Cabezas Poblet (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2003)
Background: Post-operatory pain is a spread and constant problem during the care of the surgical patient. The tendency to find new therapeutic techniques to alleviate pain has lead scientists to make and use a great variety of analgesics which are administered by different vias. The effects of narcotics on the new born are well known and the author´s worries about this problem has been the motivational point to search about the use of epidural and intratecal narcotics in the obstetric patient. Objective: To assess the use of peridural liophilized morphine in the Caesarean Section Method: A study of a series of cases was carried out at the Surgical Unit of the Gynecobstetric service of the University Hospital ¨Dr. Gustavo Aldereguía Lima¨ from February 2001 to August 2002 . This search included 120 patient who were selected to elective iterative caesarean section The variables under study were blood pressure, pulse and respiration during the pre- trans and post operative phases, onset of the anaesthetic effect and its duration, peri operatory complications , quality of the post operatory analgesia and its effect on the newborn measured by using Apgar values . The statistical procedure was developed by using the statistical package Epi Info 6. Results: The onset of the anesthetic effect and the duration of the anesthesia were not modified with the use of liophilized morphine. Vital signs remained within normal limits in most of the patients during the pre- trans and post operatory phases. The complications were: pruritus, urinary retention, nausea nad vomiting. The quality of the analgesia was satisfactory in most of the patients. The Apgar values were normal in all neonates. Conclusion: The administration of peridural liophilized morphine in elective caesarean sections is a reliable, sure and useful method in our environment.